DIAGNOSIS OF HEART DISEASE USING AUTOMATA FINITE STATE ALGORITHM - Tony Yudianto Pribadi; Kartika Handayani; Angelina Puput Giovani; Windu Gata (Jurnal Techno Nusa Mandiri, 2021)
The heart is an organ of the human body that has an important role in human life and is certainly very dangerous if our heart has problems remembering that many deaths are caused by heart disease. But with minimal knowledge and information, it is impossible to be able to maintain heart health. Therefore we need an expert who is an expert on the heart and various diseases. Based on the facts above, this research can help us to diagnose heart health and anticipate if there is a risk of heart disease by designing and implementing. This application was created using the web-based Finite State Automata algorithm which is still in the form of pseudocode. In this system several questions will be asked. After all the questions are answered, the results of the diagnosis will appear along with suggestions that can help anticipate the heart disease.